A Highly Selective Polymer Material using Benzo‐9‐Crown‐3 for the Extraction of Lithium in Presence of Other Interfering Alkali Metal Ions. Issue 9 (1st March 2021) - Oral, Iklima; Abetz, Volker
Abstract: The recovery of lithium from global water resources continues to be challenging due to interfering metal ions with similar solution properties. Hence, a lithium‐selective diblock copolymer system containing crown ethers (CEs) is developed. A polystyrene‐ block ‐poly(methacrylic acid) diblock copolymer is synthesized first via a one‐pot solution–emulsion reversible addition–fragmentation chain transfer polymerization. A subsequent Steglich esterification yields the CE functionalized polymer. The complexation properties with different alkali metals are first investigated by liquid−liquid extraction (LLE) in dichloromethane (DCM) − water systems using free benzo‐9‐crown (B9C3), benzo‐12‐crown‐4 (B12C4), and benzo‐15‐crown‐5 (B15C5) CEs as reference components, followed by the correspondingly CE‐functionalized polymers. Extraction complexation constants in the aqueous phase are determined and the impact of the complexation constants on the extractability is estimated. The B9C3 CE is especially appealing since it has the smallest cavity size among all CEs. It is too small to complex sodium or potassium ions; however, it forms sandwich complexes with a lithium‐ion resulting in extraordinary complexation constants in polymer systems avoiding other interfering alkali metal ions. On this basis, a new material for the efficient extraction of lithium ion traces in global water resources is established. Abstract : A new crown ether (CE) bound diblock copolymer based on polystyrene‐ block ‐poly(methacrylic acid) is synthesized via a one‐pot solution‐emulsion reversible addition‐fragmentation chain transfer polymerization and subsequent Steglich esterification. The complex properties of free CEs and polymer coupled CEs are investigated by calculating the complex stability constant and Gibbs free energy.